Costa Rica : Third and Final Review Under the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Costa Rica. (IMF Staff Country Reports; Country Report ;, 2010)
The 2010 staff report for the Third and Final Review Under the Stand-By Arrangement (SBA) reviews the economic performance of Costa Rica. The structural benchmarks related to the deposit insurance and bank resolution framework were delayed owing to a longer-than-expected consultation process. The gains in lowering inflation should be consolidated, including through the adoption of an inflation targeting framework to bolster policy credibility. IMF support helped to maintain confidence in the consistency of policies and the strength of financial buffers.